An analytical study of levels of innovative thinking among handball players - Zeghair, H. O.; Abbas, K. H.; Hasan, S. H. (Journal of Human Sport & Exercise, 2021)
The main objective of this paper is building and applying the scale of innovative thinking among handball players to the degree and finding standards and levels of emotional thinking among handball players. There is no doubt that there are skills that individuals share, and nevertheless there are skills in which they differ as well, and the level of variation in possessing them is an important indicator of the success of some and the failure of others. Among these skills are those that are visible to the eye, and some of them are not apparent, as they are related to the secrets of the human soul. Thinking is of great player in accordance with the requirements of the game that the player performs, especially the handball player. Of which International, skill, and psychological in addition to innovative thinking that favours his ability to do better than what makes a difference. The matter is not limited to the cognitive potential, but extends that to include the non-cognitive potential, represented by the emotional skills that have a great significance in the success of the player. Players differ in their responses to different alerts and situations depending on individual differences. The situation that includes a challenge to the player may be threatening to another player, and this is why he encourages the first to deal with this situation and tries to solve the problem that he is exposed to and sees in it an opportunity to enhance himself and his appreciation and increase his sense of self-confidence and here the role of innovative thinking is prominent in these situations. The athlete needs to think when practicing sports as the many difficult and complex situations during matches and competitions necessitate him to have an appropriate degree of intelligence, and there are differences between sports in the degree of intelligence it needs, and handball is played from complex and team games that have a special character in terms of Schematic, which requires a higher degree of intelligence, must be demonstrated by the person who practices it, handball and other games that contain a lot of planning and legal elements, And there are sports that need a degree of intelligence, however Less because it takes place in one well-known format, and also for the quality of participation with the competitor, so the more direct competition between competitors, the more innovative the athlete needs to outperform his competitor, as the short seconds and sudden movements play a role in determining the superior in the sports competition, and for this he must be adorned. The athlete has innovative thinking.